Fibroblast Growth Factor 21 Predicts and Promotes Vascular Calcification in Haemodialysis Patients - Liqiong Jiang; Qing Yin; Min Yang; Min Li; Mingming Pan; Yuchen Han; Zhen Zhao; Zhi Wang; Lili Zhu; Qing Wei; Yan Tu; Min Gao; et al. (Karger Publishers, 2021)
Background: Cardiovascular disease (CVD) is the leading cause of death in haemodialysis (HD) patients. Vascular calcification (VC) is dramatically accelerated and is strongly associated with CVD events and mortality in HD patients. VC coexists with osteoporosis in many studies. Fibroblast growth factor 21 (FGF21) which is known as an adipocytokine is a new hypoglycemic strategy and is inversely related to bone mineral density. Methods: To evaluate the contribution of FGF21 to VC in HD patients, we detected circulating FGF21 levels and measured the whole thoracic aorta calcification scores (TACS) and calcification scores of the 3 segments of thoracic aorta, including ascending thoracic aorta (ATACS), aortic arch (AoACS), and descending thoracic aorta (DTACS) of our HD patients in this cross-sectional study. In addition, we pre-incubated human aortic endothelial cells (HAECs) with FGF21 in the presence or absence of parathyroid hormone (PTH) in vitro. Results: The median serum FGF21 level in HD patients was 11-fold higher than that in healthy controls. Ln(FGF21) was positively correlated with Ln(TACS+1), Ln(ATACS+1), Ln(AoACS+1), and Ln(DTACS+1), respectively, in HD patients. Serum FGF21 was independently associated with TACS and ATACS, AoACS, and DTACS. FGF21 which was combined with age, calcium, and intact PTH demonstrated a high area under the curve of 0.84 with optimal sensitivity (84%) and specificity (71%) for the prediction of VC in HD patients. Our vitro results showed that FGF21 enhanced the calcification effect of PTH on HAECs by increasing calcium deposition and endothelial-to-mesenchymal transition. Conclusions: Circulating FGF21 was notably higher and was a potential predictor and promoter of VC in HD patients.